Long term follow-up of endovascular management of spinal cord arteriovenous malformations with emphasis on particle embolization. (3rd July 2018) - Collin, Adrien; Labeyrie, Marc-Antoine; Lenck, Stephanie; Zetchi, Akli; Aymard, Armand; Saint-Maurice, Jean-Pierre; Civelli, Vittorio; Houdart, Emmanuel
Abstract : Objective: To determine long term safety and efficacy of endovascular treatment of spinal cord arteriovenous malformations (AVMs), with calibrated particle embolization as a firstline approach. Methods: We reviewed clinical and imaging data of consecutive patients who underwent endovascular treatment for both nidal and fistulous type spinal cord AVMs in our center, from 1990 to 2015. Outcome at the last follow-up was assessed by an independent observer. Results: Embolization of spinal cord AVMs was performed in 61 patients, including 46 (75%) with particles (exclusively in 29 patients), 30 (49%) with cyanoacrylate, and 6 (10%) with combined surgical treatments. Particle embolizations were iterative in 33 patients (median number of sessions 5 (range 3–6)). Neurological deterioration after treatment occurred in 5 patients (cyanoacrylate=4, surgery=1, particles=0; P<0.001). At a median follow-up of 6 years (range 3–13 years), angiographic cure was obtained in 11/61 (18%) patients (nidal type=6/53 (11%), fistulous type=5/8 (63%)). In progressive forms, neurological improvement occurred in 16/28 (57%) patients, stabilized in 9/28 (31%), and worsened in 3/28 (12%). In hemorrhagic forms, the rebleeding rate was 4/14 patient years without standard treatment, 0/322 patient years in partial iterative treatment, and 0/15 patient years in angiographically cured lesions (P=0.001). Conclusion: Our study suggests that particle embolization as a firstline therapy to treat spinal cord AVMs is safe and offers long term efficacy, especially for those with small, distal, and multiple shunts. Partial occlusion of the AVM may be sufficient to prevent rebleeding, without the potential risks of complete occlusion. Particle calibration and injection technique, 'one by one', are critical to safety. Cyanoacrylate embolization or surgery remains necessary if particle embolization fails to occlude large shunts.